THE IMPACT OF GODEL ON AI - Shara, Jollanda (European Scientific Journal, ESJ, 2014)
In this paper we have discussed some of the main contributions of Kurt Godel on artificial intelligence(AI).We give a simple description of Godel’s Incompleteness Theorem which was,certainly,the major theorem he proved during his bright career.He is considered as one of the inventers of the theory of recursive functions which formed part of the foundations of computers,too. Godel was,of course,one of the greatest logicians ever.